A Pediatric COVID-19 Study: Retinal Nerve Fiber Layer, Ganglion Cell Layer, and Alterations in Choroidal Thickness in Swept-Source OCT Measurements - Akpolat, Cetin; Cetinkaya, Tugba; Kurt, Muhammed M. (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose To investigate early covid measurements of central macular thickness (CMT), retinal nerve fiber layer (RNFL), ganglion cell layer (GCL) thickness, and choroidal thickness (ChT) in children recovered from coronavirus disease 2019 (COVID-19).Methods This cross-sectional study was carried out 4 weeks after completed COVID-19 treatment. The diagnosis of the Alpha variant COVID-19 was made by the polymerase chain reaction test after prediagnosis with clinical, laboratory, and radiological findings. A total of 46 children were included in the study. Pediatric patients who received COVID-19 treatment comprised the COVID-19 group (24 children), and healthy children were enrolled in the control group (22 children). Only the right eyes of the participants were enrolled in the study. All pediatric patients in the COVID-19 group required hospitalization without the need for intubation. Swept-source optical coherence tomography (SS-OCT) was used to measure CMT, RNFL, and GCL thickness, and ChT measurements.Results The COVID-19 and control groups had similar mean values of visual acuity, intraocular pressure, spherical equivalent, axial length, and CMT (p > 0.05 for all). RNFL thickening, GCL, and choroidal thinning were observed in all SS-OCT measurements of COVID-19 children. However, RNFL thickening was significant only in the global and nasal peripapillary quadrants. GCL thinning was significant in the nasal/inferior sector (p < 0.002 for all). Some significant correlations were observed between the mean levels of inflammatory markers and OCT measurements (p < 0.002).Conclusion This study may be among the first reports of SS-OCT examination of COVID-19 children. OCT measurements showed changes in retinal and ChT in the COVID-19 children as in adult patients.
Keywords: pediatric COVID-19; retinal neurodegeneration; swept-source; optical coherence tomography